Instability of mixed Nash equilibria in generalised Hawk-Dove game: A project conflict management scenario - Sheryl Le Chang; Mikhail Prokopenko (Games, 2017)
This paper generalises the Hawk-Dove evolutionary game by introducing cost sharing ratios for both players, and applies the generalised Hawk-Dove model to conflict management in projects through investigating the stability of Nash equilibria. A model with clashing interests between a project owner and a contractor is considered to derive their strategy adaptation given the cost sharing ratios. As expected, the pure Nash equilibria are shown to be dominantly stable while the mixed strategy equilibrium is observed to be unstable, across the range of considered cost sharing ratios. In addition, simulations are conducted on the strategy adaptation and stability of the equilibria under noisy and latent conditions. The obtained results can be used by project managers in optimising their strategy in practice.
Keywords: 330; evolutionary game theory; project conflict management; Nash equilibrium; Hawk-Dove game